Exploring Students’ Perceptions of AI in Self-Directed Speaking Practice: A Case Study at STKIP Taman Siswa Bima - Al Farizy, Salman; Khatimah, Khusnul; Irawati , Ika (Journal of Educational Sciences, 2025)
The advancement of Artificial Intelligence (AI) has significantly transformed language learning, offering innovative solutions for autonomous skill development, particularly in speaking. This study aims to explore students’ perceptions of AI integration, specifically through the CICI AI platform, in self-directed English speaking practice. Employing a descriptive qualitative method with a case study design, data were collected from English Education students at STKIP Taman Siswa Bima through questionnaires, semi-structured interviews, and observations. The Technology Acceptance Model (TAM) was used as the theoretical framework to examine perceived usefulness and ease of use. Findings indicate that most students perceived AI as beneficial for improving speaking confidence (M = 3.53) and motivation (M = 3.47), with overall ease of use rated highly (M = 4.0). Despite these positive perceptions, students reported several challenges, including unstable internet access (87%), difficulty in pronunciation recognition (80%), and limited contextual feedback. The study concludes that while AI facilitates flexible and personalized speaking practice, its effectiveness depends on technical stability and user readiness. These insights highlight the importance of developing AI tools that are not only user-friendly but also responsive to learners’ linguistic diversity and emotional engagement in language learning.